Unity in diversity: a survey of muscular systems of ctenostome Gymnolaemata (Lophotrochozoa, Bryozoa) - Thomas F. Schwaha; Andreas Wanninger (Frontiers in Zoology, 2018)
Abstract Background Myoanatomical studies of adult bryozoans employing fluorescent staining and confocal laser scanning microscopy (CLSM) have been chiefly conducted on freshwater bryozoans. The diversity of muscular systems in the marine bryozoans is currently not well known with only two species being studied in more detail. The aim of this study is to unravel the diversity of muscle systems of 15 ctenostome bryozoans by phalloidin-coupled fluorescence stainings combined with CLSM. Results In general, the myoanatomy of the selected ctenostomes shows significant similarities and consists of 1) muscles associated with the body wall, 2) apertural muscles, 3) lophophoral muscles, 4) tentacle sheath muscles, 5) digestive tract muscles and 6) the prominent retractor muscles. Differences are present in the arrangement of the apertural muscles from generally three muscles sets of four bundles, which in some species can be partially reduced or modified into a bilateral arrangement. The cardiac region of the digestive tract shows a distinct sphincter in four of the six studied clades. In some cases the cardiac region forms a prominent proventriculus or gizzard. Tentacle sheath muscles in victorelloideans and walkerioideans are arranged diagonally and differ from the simple longitudinal muscle arrangements common to all other taxa. Lophophoral base muscles consist of four sets that vary in the size of the sets and in the shape of the inner lophophoral ring, which either forms a complete ring or separate, intertentacular muscle bundles. The stolon-forming walkeridiodean ctenostomes show prominent transverse muscles in their stolons. These are always present in the shorter side stolons, but their occurrence in the main stolon seems to depend on the colony form, being present in creeping but absent in erect colony forms. Conclusions This study represents the first broad survey of muscular systems in adult ctenostome bryozoans and shows a certain degree of conservation in a series of diverse colony forms belonging to five major clades. However, several myoanatomical features such as the cardiac sphincter, basal (possibly transitory) cystid muscles, tentacle sheath muscles or apertural muscle arrangement vary across taxa and thus show a high potential for the assessment of character evolution within ctenostomes. As such, this study represents an essential contribution towards determining and reconstructing the character states of the bryozoan ground pattern once a reliable phylogenetic tree of the whole phylum becomes available.